Ion exchange dependent electroactive phase content and electrical properties of poly(vinylidene fluoride)/Na(M)Y composites - Lopes, A. C. (2015)
Different metal-ion exchanged NaY zeolite, Na(M)Y, were used to prepare poly(vinylidene fluoride) based composites by solvent casting and melting crystallization. The effect of different metal ion-exchanged zeolites on polymer crystallization and electrical properties was reported. Cation-framework interactions and hydration energy of the cations determined that K+ is the most efficient exchanged ion in NaY zeolite, followed by Cs+ and Li+. The electroactive phase crystallization strongly depends on the ions present in the zeolite, leading to variations of the surface energy characteristics of the Na(M)Y zeolites and the polymer chain ability of penetration in the zeolite. Thus, Na(Li)Y and NaY induces the complete electroactive -phase crystallization of the crystalline phase of PVDF, while Na(K)Y only induces it partly and Na(Cs)Y is not able to promote the crystallization of the electroactive phase. Furthermore, different ion size/weigh and different interaction with the zeolite framework results in significant variations in the electrical response of the composite. In this way, iinterfacial polarization effects in the zeolite cavities and zeolite-polymer interface, leads to strong increases of the dielectric constant on the composites with lightest ions weakly bound to the zeolite framework. Polymer composite with Na(Li)Y show the highest dielectric response, followed by NaY and Na(K)Y. Zeolite Na(Cs)Y contribute to a decrease of the dielectric constant of the composite. The results show the relevance of the materials for sensor development.